Zadie Smith’s White Teeth: Dubious Existence of Cultural Authenticity - Panta, Shiva Raj (Literary Studies, 2021)
This paper argues the cultural authenticity is a questionable conception. Zadie Smith’s debut novel, White Teeth features characters like Samad Miah Iqbal and Hortense Bowden who aredetermined toretain cultural purity. Through this projection,presumably, Smith intends to satirize their efforts and substantiates her claim that cultural purity cannot maintained, especially, when the immigrants come to the host country. Despite the guarding of one’s culture, the breaching of the cultural integrity has visibly taken place in the novel